2020
DOI: 10.3390/ijerph17093237
|View full text |Cite
|
Sign up to set email alerts
|

How Incivility and Academic Stress Influence Psychological Health among College Students: The Moderating Role of Gratitude

Abstract: Many students suffer from academic stress and uncivil behaviors at colleges and there is a need to identify to what extent these negative phenomena might impact students’ mental health. The main purpose of this study is to examine the relationships between incivility, academic stress, and psychological health, as well as investigate the moderating role of gratitude. The study design of this research is cross-sectional. The final sample consisted of 895 university students in China; The Statistical Package for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…It is demonstrated in this study that hindrance stress is associated with mental and physical costs, including depersonalization, which supports the demand-control model model. Second, research on stress, servant leadership, and employees' well-being still remains scarce in both leadership and health literature, especially in the context of education [47,48]. Therefore, this research adds to the literature by extending our understanding of how servant leadership impacts the power of the relationship between stress and employees' well-being.…”
Section: Discussionmentioning
confidence: 96%
“…It is demonstrated in this study that hindrance stress is associated with mental and physical costs, including depersonalization, which supports the demand-control model model. Second, research on stress, servant leadership, and employees' well-being still remains scarce in both leadership and health literature, especially in the context of education [47,48]. Therefore, this research adds to the literature by extending our understanding of how servant leadership impacts the power of the relationship between stress and employees' well-being.…”
Section: Discussionmentioning
confidence: 96%
“…As far as health consequences are concerned, academic stress is associated with physical and psychological symptoms, such as impaired appetite, sleep disturbances, headaches and increased heart rate [48,49]. The correlation between academic stress and wellbeing is not surprising [50]. Stressful stimulus can, therefore, interfere with academic preparation, concentration and performance [51].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In some cases, students resort to extreme deviant behaviors such as suicide, run-away from home, drug addiction break institutional rules and procedures (Garg and Saxena, 2020). Huang et al (2020) study how uncivil behavior and academic stress influence the psychological health of the student. Busari (2012) suggested that a stressed mind and body make it difficult for a student to concentrate.…”
Section: Literature Reviewmentioning
confidence: 99%